CSF metabolites associate with CSF tau and improve prediction of Alzheimer's disease status. Issue 1 (1st May 2021) - Dong, Ruocheng; Darst, Burcu F.; Deming, Yuetiva; Ma, Yue; Lu, Qiongshi; Zetterberg, Henrik; Blennow, Kaj; Carlsson, Cynthia M.; Johnson, Sterling C.; Asthana, Sanjay; Engelman, Corinne D.
Abstract: Introduction: Cerebrospinal fluid (CSF) total tau (t‐tau) and phosphorylated tau (p‐tau) are biomarkers of Alzheimer's disease (AD), yet much is unknown about AD‐associated changes in tau metabolism and tau tangle etiology. Methods: We assessed the variation of t‐tau and p‐tau explained by 38 previously identified CSF metabolites using linear regression models in middle‐age controls from the Wisconsin Alzheimer's Disease Research Center, and predicted AD/mild cognitive impairment (MCI) versus an independent set of older controls using metabolites selected by the least absolute shrinkage and selection operator (LASSO). Results: The 38 CSF metabolites explained 70.3% and 75.7% of the variance in t‐tau and p‐tau, respectively. Of these, seven LASSO‐selected metabolites improved the prediction ability of AD/MCI versus older controls (area under the curve score increased from 0.92 to 0.97 and 0.78 to 0.93) compared to the base model. Discussion: These tau‐correlated CSF metabolites increase AD/MCI prediction accuracy and may provide insight into tau tangle etiology.